REKRUTMEN BERDASARKAN MERITOKRASI DAN DAMPAKNYA TERHADAP TATA KELOLA DESA DI INDONESIA - Munir, Mohamad; Harto, Unggul Sugi; Zainudin, Arif (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
This article investigates the dynamics of implementing meritocracy-based recruitment for village officials in Indonesian governance. Despite national regulations mandating objective and transparent selection procedures, implementation is significantly challenged by the dominance of local politics, patronage, and weak internal oversight, impacting overall accountability. This study employs a qualitative approach, utilizing empirical data from 2023–2024 field observations, Indonesian Ombudsman reports, and case studies across various districts. The primary objective is to develop a conceptual and operational framework for village official selection based on the principles of legality, public participation, and digital technology. The findings show that the presence of reformist actors (village heads, academics, and LSM) is a crucial catalyst. These actors promote competency-based selection and establish effective checks and balances, demonstrably enhancing the legitimacy and accountability of recruitment results. However, entrenched socio-political contexts, particularly strong patron-client structures and kinship-based cultures, remain major obstacles to the full implementation of meritocracy. This article proposes a conceptual and operational framework for merit-based selection founded on participatory principles, legality, and digital technology. It concludes by suggesting the necessity of institutional strengthening and state intervention to ensure fair and professional selection across all regions.